FAKTOR- FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL APARAT PEMERINTAHAN ( STUDI KASUS PEMERINTAH DAERAH INDRAMAYU) - Ita Friyanty (Universitas Mercu Buana, 2016)
ABSTRACTBudget is an important element in the control system for budget management not only as a financial planning tool, but also as a means of control, coordination, communication, performance evaluation and motivation. The concept of budgeting styles include characteristics that budget targets a budget participation, budget clarity and feedback budget, and budget evaluation. The importance of an effective internal control system will affect managerial performance of local government officials so that organizational goals can be achieved. Keywords: budget participation, budget clarity, feedback, evaluation of the budget, internal control system of government, performance.